Micro enterprises, self-efficacy and knowledge acquisition: evidence from Greece and Spain. Issue 3 (10th October 2018) - Duarte Alonso, Abel; Kok, Seng; Sakellarios, Nikolaos; O'Brien, Seamus
Abstract : Purpose: The purpose of this exploratory study is to investigate the significance of self-efficacy and knowledge acquisition among micro businesses operating in challenging economic environments. The study uses social cognitive theory (SCT) and the knowledge-based theory of the firm (KBTF), and it proposes a refinement of these theoretical frameworks in the context of the study. Design/methodology/approach: A case method was chosen, and face-to-face interviews with 14 owners of firms in island and rural regions of Greece and Spain were conducted. Findings: Content analysis identified the importance of self-efficacy, primarily illustrated by entrepreneurs' determination and self-motivation, propensity to take risks and ability to anticipate consequences of their actions. Acquisition and accumulation of explicit knowledge, particularly through generational or mentoring processes, and subsequent wealth of tacit knowledge, also emerged as very significant in preparing and guiding entrepreneurs. Various links between the adopted theories and findings emerged, particularly regarding forethought, vicarious learning (SCT) and specialisation in knowledge acquisition (KBTF). Originality/value: The proposed theoretical refinement based on the SCT and KBTF paradigms allows for a more rigorous, in-depth reflection on the links between cognitive elements present in the participating micro entrepreneurs and knowledge-based attributes on their ability to increase organisational resilience. The study also contributes toward the micro business literature and addresses a knowledge gap, particularly, in that contemporary research has not explored entrepreneurial motivations among small firm entrepreneurs. Finally, the practical implications emerging from the findings provide a platform for various stakeholders (associations, government agencies) to appreciate and support entrepreneurs' needs, notably, of acquiring, increasing and sharing knowledge.